Promosi Kesehatan Bagi Lansia Dengan Gejala Stroke Dalam Latihan Terapi Cermin Untuk Meningkatkan Kekuatan Otot Wajah Dikelurahan Barusari Kota Semarang - Ainnur Rahmanti; Margiyati Margiyati; Anisa Mutiara Hanani; Panji Satria Wiguna; Eriga Yessyra Syafitri; Dana Faricha; Auliya Rahma Putri (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2023)
According to the Law of the Republic of Indonesia number 13 of 1998 concerning elderly welfare, an elderly person is someone who has reached the age of 60 years and above. Indonesia alone ranks fourth in the world with 24 million elderly people who have not received much attention. The decline in various body functions in old age can cause elderly people to have difficulty eating due to various causes. For example, the appetite of the elderly tends to decrease because their sense of taste and smell is no longer as sharp as it used to be to inhale aromas and taste food. The elderly are also more prone to decreased saliva production, loose teeth, weakened intestinal and gastric functions, and decreased stomach acid production which makes it difficult for the body to absorb food. Weakness or paralysis of the face, also known as facial frown, will cause impairment in the ability of facial muscles. Miror Therapy exercises can help improve facial muscle strength in patients with stroke. Regular exercise for 2 times a week can help increase the muscle strength of stroke patients.